An in-depth investigation on the presence of methanol in Garcinia cambogia fruits and rinds: Role of pectin methyl esterase and indigenous fungi - Abhijeet Bhimrao Muley; Ketan Mulchandani; Rekha Satishchandra Singhal (Food Chemistry Advances, 2024)
The presence of methanol in fruits is a concern due to its toxicity and the consequent health implications. Garcinia cambogia fruits and Garcinia cambogia rinds showed methanol at 238 ± 15.07 and 355 ± 18.21 ppm, respectively. The enzyme, pectin methyl esterase (PME), associated with production of methanol was also detected with an activity 5.63 ± 0.41 and 2.75 ± 0.14 U/mL, respectively, in fruits and rinds. Furthermore, a fungi isolated from Garcinia cambogia, and identified as Aspergillus aculeatus by morphology and 18S rRNA gene/ITS/D1-D2 (∼700 bp) sequencing, also produced extracellular PME (7.67 ± 0.76 U/mL) at pH 3 to yield 166 ± 5.74 ppm methanol. The molecular weight of partially purified PMEs with 60–70 % ammonium sulphate from G. cambogia fruits, G. cambogia rinds and A. aculeatus of was ∼45, ∼25, and ∼35 kDa, could produce 55.33 ± 2.74, 41.67 ± 0.86, and 74.67 ± 0.19 ppm methanol, and displayed maximum activity at pH 7, 7 and 5, and 35 °C, 35 °C and 40 °C, respectively. The enzyme kinetics, (Km and Vmax), thermal inactivation kinetic parameters (kd, t1/2 and d-value), and thermodynamic parameters (Ed, ΔH°, ΔG°, and ΔS°) of PME from A. aculeatus were superior over PME from G. cambogia fruits and G. cambogia rinds. This investigation confirmed the production of both PME and methanol by both fungi and G. cambogia.